Monoterpene-Containing Substituted Coumarins as Inhibitors of Respiratory Syncytial Virus (RSV) Replication - Khomenko, Tatyana M.; Shtro, Anna A.; Galochkina, Anastasia V.; Nikolaeva, Yulia V.; Petukhova, Galina D.; Borisevich, Sophia S.; Korchagina, Dina V.; Volcho, Konstantin P.; Salakhutdinov, Nariman F. (Molecules (Basel, Switzerland), 2021)
Respiratory syncytial virus (RSV) is a critical cause of infant mortality. However, there are no vaccines and adequate drugs for its treatment. We showed, for the first time, that O-linked coumarin–monoterpene conjugates are effective RSV inhibitors. The most potent compounds are active against both RSV serotypes, A and B. According to the results of the time-of-addition experiment, the conjugates act at the early stages of virus cycle. Based on molecular modelling data, RSV F protein may be considered as a possible target.